IRIBAN DALAM EKONOMI KAMPUNGAN Studi Kasus di Desa Jambu, Mlonggo, Jepara - Hasanah, Siti (Fakultas Ilmu Budaya Universitas Diponegoro, 2017)
Among villagers of Jambu, in Mlonggo subdistrict of Jepara regency, there is iriban activity that has become a tradition in their daily lives. This routine includes neighborhood meeting on the date of 15th and 30th, participated by men and women as members of the neighborhood association (Rukun Tetangga); the other activities are only participated by the men such as dhiba'an or berjanjen held every Sunday evening, the manaqiban held on the date of 11th and 27th as well as tahlilan held every Thursday night. Iriban activity has become a tradition that is carried out from generation to generation. Yhe reason for the implementation of iriban tradition is to draw the spirit and sympathy of the people to participate in social activities. The implementation of iriban philosophy includes some elements, such as paguyuban (gemeinschaft) and patembayan (gesselschaft) concepts, reciprocity, exchange theory, and togetherness.